Space-Selective Control of Functional Crystals by Femtosecond Laser: A Comparison between SrO-TiO2-SiO2 and Li2O-Nb2O5-SiO2 Glasses - Xuan He; Qiming Liu; Matthieu Lancry; François Brisset; Bertrand Poumellec (Crystals, 2020)
We report on space-selective crystallization of congruent and polar Sr2TiSi2O8 crystals in a stoichiometric SrO-TiO2-SiO2 glass induced by (1030 nm, 300 fs) femtosecond laser irradiation. This allows us to compare with non-congruent laser-induced crystallization of polar LiNbO3 in non-stoichiometric Li2O-Nb2O5-SiO2 glass and gain information on the mechanism of nanocrystals orientation with the laser polarization that we pointed out previously. Using scanning electron microscopy (SEM), second harmonic generation (SHG), and electron backscattered diffraction (EBSD), we studied the laser-induced crystallization according to the laser processing parameters (pulse energy, pulse repetition rate, scanning speed). We found (1) a domain where the laser track is filled with crystals not perfectly textured (low energy), (2) a domain where an amorphous volume remains surrounded by a crystallized shell (high energy). This arises from Sr out-diffusion and may give rise to the crystallization of both SrTiO3 and Sr2TiSi2O8 phases at low speed. In the one-phase domain (at higher speed), the possibility to elaborate a tube with a perfect Fresnoite texture is found. A significant difference in size and morphology whereas the crystallization threshold remains similar is discussed based on glass thermal properties. Contrarily to Li2O-Nb2O5-SiO2 (LNS) glass, no domain of oriented nanocrystallization controlled by the laser polarization has been found in SrO-TiO2-SiO2 (STS) glass, which is attributed to the larger crystallization speed in STS glass. No nanogratings have also been found that is likely due to the congruency of the glass.